Traetment Model Take and Give terhadap Retensi Siswa dalam Nama Istilah Biologi pada Materim Ekosistem di Madrasah Tsanawiyah Asas Islamiyah - Rizki Fitri Astuti (EDU-BIO: Jurnal Pendidikan Biologi, 2018)
The learning process at Madrasah Tsanawiyah Asas Islamiyah Sipin Kota Jambi still uses the learning model of teacher center learning so that the students do not understand the name of biology term especially their ecosystem material difficulties in memorizing and memories in their memory. Take and give model is a learning process that seeks to associate new knowledge with knowledge that has been owned by students. This research is a quantitative research using Posstest Only Control design design. The result of test data analysis of test "t" is obtained t0 = 3,24 while ttabel at significance level 5% = 2.01 and ttable at significance level 1% = 2.68 then t0 is bigger than ttable or 2.01 ≤ 3, 24 ≥ 2.68. And the retention percentage is obtained from the experimental class of 62.96% and the control class is 56.15%. Thus there is a significant difference between students using take and give model with students who do not use take and give model in their learning process toward student retention. Keywords: Take and give model, Student Retention